Mosby's physical examination DVD series : DVD 9 : breast and axillae [ - Ball, Jane; Benedict, G. William; Dains, Joyce E.; Seidel, Henry M. (Mosby's physical examination DVD series, 2006)
This 13 minute video shows the steps needed to examine the breasts and axillae, including the proper use of equipment. With the patient seated, it demonstrates how to inspect the patient's breasts in four positions and how to palpate the breasts and axillae. With the patient supine, it shows various patterns for completing palpation of the breasts. The video highlights expected findings and alerts the viewer to selected variations in pediatric and geriatric patients. In addition, it emphasizes the importance of patient teaching regarding breast self-examination."-- Publisher's website